2011
DOI: 10.1093/annonc/mdq738
|View full text |Cite
|
Sign up to set email alerts
|

Which patients benefit most from adjuvant aromatase inhibitors? Results using a composite measure of prognostic risk in the BIG 1-98 randomized trial

Abstract: A composite measure of risk informs treatment selection better than individual biomarkers and supports the choice of 5 years of letrozole for patients at highest risk for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 19 publications
3
52
0
4
Order By: Relevance
“…A number of studies have investigated tumor biomarkers that indicated differential benefit from aromatase inhibitors versus tamoxifen in patients with early breast cancer (4)(5)(6). Such biomarkers included the conventional factors, estrogen receptor (ER), progesterone receptor (PgR), human epidermal growth factor receptor type 2 (HER2) and Ki-67, and did not identify patients who derived a differential relative benefit from aromatase inhibitors over tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated tumor biomarkers that indicated differential benefit from aromatase inhibitors versus tamoxifen in patients with early breast cancer (4)(5)(6). Such biomarkers included the conventional factors, estrogen receptor (ER), progesterone receptor (PgR), human epidermal growth factor receptor type 2 (HER2) and Ki-67, and did not identify patients who derived a differential relative benefit from aromatase inhibitors over tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the selection criteria of adjuvant treatment in patients with the ER+/HER2-subtype is particularly difficult to define. Patients who are at high risk for recurrence need to be distinguished from those at low risk, for whom adjuvant aromatase inhibitors may be sufficient (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…[11] The predictive and prognostic value of PR expression in ER negative cancers is much less understood, mostly because of the rarity of this disease subset.…”
mentioning
confidence: 99%
“…En el meta-análisis citado previamente el beneficio de la TE adyuvante fue similar en pacientes con RE+ versus aquellos con RE-y RP+ 8 . Tumores RE+/ RP-pueden reflejar la activación de vías de señales de crecimiento y los IA podrían ser más efectivos que el tamoxifeno en esta población 31 .…”
Section: Bio-marcadores Clásicos En CMunclassified